Predictors of Intensive Care Unit Admission Following Cytoreductive Surgery For Stage III-IV Ovarian Carcinoma - Cafer Kaplan; Coşkun Araz; Selim Candan; Arash Pirat; Pınar Zeyneloğlu; Ali Ayhan; Gülnaz Arslan (Galenos Yayinevi, 2012)
Objective: To demonstrate that preoperative and intraoperative data of ovarian carcinoma patients can be used for prediction of postoperative ICU admission. Material and Method: The charts of all patients with ovarian carcinoma who underwent cytoreductive surgery from January 2007 to December 2009 were reviewed. The data recorded were demographic features, co-existing disease, preoperative laboratory findings, intraoperative data, and admission/no admission to ICU postoperatively. Results: Out of 122 patients who underwent cytoreductive surgery for advanced ovarian carcinoma, 58 patients (48%) required ICU admission postoperatively. Compared with the group not admitted to ICU, the patients with ICU admission were significantly different regarding the frequency of chronic obstructive pulmonary disease, occurrence of intraoperative hypotension and sinus tachycardia, intraoperative need for blood products and total fluid transfusion, preoperative oxygen saturation, mean age and mean body mass index (BMI). Binary logistic regression analysis revealed that age (OR, 1.1; p=0.036), ASA score (OR, 6.2; p=0.044), occurrence of intraoperative sinus tachycardia (OR, 8.6; p=0.013), need for intraoperative transfusions (OR, 7.7; p=0.026) and preoperative oxygen saturations (OR, 1.3; p=0.050) were the predictors of ICU admission in these patients. Conclusion: The results suggest that age, high ASA scores, low preoperative oxygen saturations, intraoperative sinus tachycardia and blood product transfusions were predictors of ICU admission following cytoreductive surgery for ovarian carcinoma.